IMPLEMENTASI SUPERVISI BERBASIS DATA PADA BIMBINGAN DAN KONSELING DI SMA: STUDI KASUS - Siti Qurotul A'yun; Navyta Ramadhani Bukhroni Putri; Jannatus Syarifah; Moh. Sholeh Murahman; Titin Indah Pratiwi; Bambang Dibyo Wiyono (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to provide an in-depth understanding of the implementation of data-driven supervision in school counseling services and its contribution to improving service quality. Employing a qualitative approach with a case study design, the research involved school principals, supervisors, and guidance and counseling teachers who were purposively selected due to their direct engagement in the supervision process. Data were obtained through in-depth interviews, supervision observations, and document reviews, including student needs assessments, counseling journals, and case reports. The data were analyzed through stages of data reduction, thematic categorization, interpretation, and triangulation to ensure accuracy and credibility. The results indicate that data-driven supervision is carried out systematically through a sequence of pre-conference, observation, post-conference, and follow-up meetings, enabling professional development to occur objectively based on empirical evidence rather than subjective judgment. The novelty of this study lies in its empirical mapping of the integration between clinical supervision and scientific supervision within data-driven supervision practices in school counseling, a topic that remains underexplored in the Indonesian context. Overall, data-driven supervision enhances the precision of service planning, the quality of documentation, and the relevance of interventions to student needs, and has the potential to evolve into a continuous professional development model when supported by improved digital literacy and a reflective, collaborative school culture.